A Novel Three-Dimensional Culture Device Favors a Myelinating Morphology of Neural Stem Cell-Derived Oligodendrocytes - Flagelli, Alessandra; Candini, Olivia; Frabetti, Stella; Dominici, Massimo; Giardino, Luciana; Calzà, Laura; Baldassarro, Vito Antonio (Frontiers in Cell and Developmental Biology, 2021)
The complexity of the central nervous system (CNS) requires researchers to consider all the variables linked to the interaction between the different cell inhabitants. On this basis, any in vitro study of the physiological and pathological processes regarding the CNS should consider the balance between the standardization of the assay and the complexity of the cellular system which mimics the in vivo microenvironment. One of the main structural and functional components of the CNS is the oligodendrocyte precursor cell (OPC), responsible for developmental myelination and myelin turnover and repair during adulthood following differentiation into mature oligodendrocytes. In the present brief research report, we describe a 3D culture tool (VITVO) based on an inert and biocompatible synthetic polymer material scaffold, functionalized with laminin coating, and tested as a new culture microenvironment for neural stem/precursor cell (NSPC) differentiation compared to standard 2D cultures. NSPCs spontaneously differentiate in the three neuronal lineages (neurons, astrocytes and OPCs), identified by specific markers, along the fibers in the 3D structure. Analysis of the mRNA levels for lineage differentiation markers reveals a higher expression compared to those seeded on a 2D surface, suggesting an acceleration of the differentiation process. We then focused on the oligodendrocyte lineage, showing that in VITVO, oligodendrocytes exhibit a myelinating morphology, proven by 3D image elaboration, linked to a higher expression of mature oligodendrocyte markers. This preliminary study on an innovative 3D culture system is the first robust step in producing new microenvironment-based strategies to investigate in vitro OPC and oligodendrocyte biology.